Library Service Platforms (LSPs) Characteristics Classification and Importance Ranking through DELPHI Method Application. Issue 4 (7th January 2022) - Kouis, Dimitrios; Agiorgitis, Georgios
Abstract: The purpose of this research is to identify the innovative features of the LSPs that differentiate them from the LMS, as well as to evaluate their importance, based on the opinions of the Greek information scientists. The method used is the Delphi 2-round questionnaire. The results show that the experts most value an all-in-one system that incorporates all modules within it, instead of different collaborating software. Interoperability between systems, the adoption of new metadata standards, the SaaS architecture and the multi-tenant model are also held in high regard. In contrast, the use of the mobile library applications feature has achieved low ranking.